2013
DOI: 10.3109/10717544.2013.839128
|View full text |Cite
|
Sign up to set email alerts
|

Penetration profile and human cadaver skin distribution of finasteride from vesicular nanocarriers

Abstract: The skin accumulation of therapeutic agents affects the efficiency of topical drug delivery. In this study, in vitro distribution of finasteride of ethosomes and liposomes in human cadaver skin after percutaneous delivery were investigated. Experiments were performed using modified Franz diffusion cells. Finasteride ethosomes, liposomes or hydroethanolic solutions were used as donor medium. Drug distribution at different skin layers and depths were studied by hotplate separation and frozen horizontal slicing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…These data support the study reported by Rao et al. ( 2015 ) and also confirmed that ethanol can reduce the time needed for a drug to reach steady state (Rao et al., 2015 ).…”
Section: Resultssupporting
confidence: 91%
“…These data support the study reported by Rao et al. ( 2015 ) and also confirmed that ethanol can reduce the time needed for a drug to reach steady state (Rao et al., 2015 ).…”
Section: Resultssupporting
confidence: 91%
“…The slope of the linear portion in the plot was calculated as the flux (μg/h/cm 2 ) (Ibrahim et al., 2015 ; Salah et al., 2017 ). The lag time was calculated by extrapolating the linear portion to the X-axis of the plot (Rao et al., 2015 ; Salah et al., 2017 ). Non-compartmental analysis was performed using the WinNonlin software (Version 4.0; Certara USA Inc., Princeton, NJ) to determine the in vivo pharmacokinetic parameters.…”
Section: Methodsmentioning
confidence: 99%